Short term active/reactive operation planning in market environment using simulated annealing - J. T. Saraiva (2003)
This paper addresses the short-term allocation of active/reactive power supplies in transmission systems in a market environment. The basic issue addressed by most papers is related to market mechanisms involving active power either in terms of a pool or by bilateral contracts. However, in several countries Volt/Var control started to be considered, at least partially, as a marketable service and so new methodologies are required to support this process. This paper presents an integrated mathematical formulation for the active power dispatch using bids from market agents and inherently taking into account the local nature of Volt/Var control by considering an AC model for the network. The discrete operation of several components as transformer taps and capacitor sections are accurately taken care by using Simulated Annealing. The proposed methodology is applied on the 30-bus IEEE test system highlighting its advantages and demonstrating the feasibility of its use in real systems.